Unconventional myosins muscle into myofibrils - Luna, Elizabeth J. (J Biol Chem, 2019)
“Myosin” is famous as a component of muscle fibrils, but the majority of myosin family members act elsewhere with roles unrelated to muscle contraction. The biological functions of a relatively new family of these unconventional myosins, myosins 18A and 18B, are poorly understood. New research from Horsthemke et al. describes a new isoform (Myo18Aγ) that is essential for heart function and viability in mice. Their findings both support and contradict other work in the field and raise new questions about the roles of myosin 18 proteins in vivo.